PENGARUH KEDISIPLINAN TERHADAP PRESTASI BELAJAR PAI DAN BUDI PEKERTI PADA SISWA KELAS X DI SMA NEGERI 1 BANUHAMPU KABUPATEN AGAM - Fadillah Husnah; Endri Yenti (CV. ADIBA AISHA AMIRA, 2025)
This research was motivated by some class X students at SMA Negeri 1 Banuhampu who lacked discipline in studying. The formulation of the problem in this research is how much influence discipline has on the learning achievement of PAI dan Budi Pekerti in class X students at SMA Negeri 1 Banuhmapu. The aim of carrying out this research is to find out how much influence discipline has on the learning achievement of PAI dan Budi Pekerti in class This research method is a kuantitatif research method with a survey type. The population in this study was 280 people with a sample of 70 people. The data collection technique used is by collecting data on students' Semester 1 Examination scores and distributing questionnaires regarding discipline. The data analysis technique used is Simple Linear Regression analysis. The research results showed that a constant (a) value was 44,919. The discipline coefficient (variable X) is 0,427. So the regression equation Y=44,919 + 0,427X is obtained, and the significance value is 0.05 < 0.001 and tcount > ttable, namely 5,906 > 1.667. In accordance with the criteria thitung > ttable then H0 is rejected and Ha is accepted. This means that there is a significant influence between discipline on PAI Budi Pekerti learning achievement in class X students at SMA Negeri 1 Banuhampu. And R Square is 0,339. This means that the discipline variable has an influence of 33,9% on the learning achievement variables PAI dan Budi Pekerti in class X students at SMA Negeri 1 Banuhampu.